Развитие экономики республики Каракалпакстан в контексте региональной политики Узбекистана (SCIENCE and SOCIETY, 2018)
In the article, based on the requirements of the modernity of the innovation period, economic development of the regions of Uz- bekistan is considered. Guided by the fundamental requirements of the regional policy of the republic, are indicated. The need to ac- celerate the industrial development of regions in particular the Lower Amudarya economic region. On the example of the republic of Karakalpakstan, adhering to the decisions of the visiting session of the government of the republic of Uzbekistan in the city of Nukus the expediency of integrated development and use of fuel and energy, mineral and other recources are advised with the purpose of the acceleration of industrial development of the republic of Karakalpakstan.